The Identification and Prioritization of the Factors Affecting Corporate Social Responsibility Implementation in the Construction Industry—The Perspective of Developing Countries - Yunxia Ran; Azlan Shah Ali; Liyin Shen; Hafez Bin Salleh; Mingli Zhu; Kaiyi Li; Rui Wang; Yu Cao (Buildings, 2025)
Corporate social responsibility (CSR) has become a vital component in addressing environmental, social, and economic challenges. In the context of the construction industry, due to the widespread presence of irresponsible practices, CSR implementation studies have gained significant attention, particularly in developing countries. This study consists of a systematic literature review of 58 articles published between 2018 and 2024, seeking to explore the internal and external factors affecting CSR implementation in emerging construction nations. The analysis employs the PESTEL framework, which refers to external impact factors, including political, economic, social, technological, environmental, and legal aspects. Additionally, the SWOT framework is utilized to identify the strength, weaknesses, opportunities, and threats. The Analytic Hierarchy Process (AHP) is then applied to prioritize the identified factors. The results demonstrate that institutional pressures and economic progress are the most influential external opportunities. Internal weaknesses, including subcontracting and quality challenges and financial constraints of SMEs, are significant barriers. This study contributes to the CSR literature by integrating external macro-environmental factors and internal organizational dynamics, offering a strategic and actionable framework for the advancement of CSR implementation in the construction industries of developing countries.